2004
DOI: 10.1007/s10029-003-0162-9
|View full text |Cite
|
Sign up to set email alerts
|

Inguinal hernia on the Internet: A critical comparison of Germany and the U.K.

Abstract: Despite containing an increasing amount of medical information, the Internet provides only rare benefits for surgical patients. Using "inguinal hernia" as a catchword, an amateur search was imitated on the British Internet market. Sixty-five pages, standardised regarding quality and efficiency, were evaluated. A comparison to the German Internet market was added. In summary, the broad majority of the pages revealed poor results. Technical appearance, quality of content, and target grouping show big deficiencie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
4
0

Year Published

2004
2004
2011
2011

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 16 publications
0
4
0
Order By: Relevance
“…[3][4][5][6] Poor results were also seen in web searches for as imples urgicals earch phrase like'inguinalhernia'. 13 Thereismuch variabilityinthe available informationwith regards to surgical treatment options and surgical complications.…”
mentioning
confidence: 99%
“…[3][4][5][6] Poor results were also seen in web searches for as imples urgicals earch phrase like'inguinalhernia'. 13 Thereismuch variabilityinthe available informationwith regards to surgical treatment options and surgical complications.…”
mentioning
confidence: 99%
“…8 Previous work found gross insufficiency when searching the internet for UK web pages offering information on inguinal hernia repair:the information provided was poor quality,did not aid patients on decisionmaking and in most cases the authorship was non-transparent. 6 In comparison NHS web pages are free of advertising, have an author and the information provided should be reproducible.In this study we found that variability does exist in both the quality and availability of information provided by NHS hospital websites.…”
Section: Discussionmentioning
confidence: 99%
“…5 Previous work has indicated that availability of internet information in the UK is from mixed sources including providers of surgical services and industry-funded sources, and in most cases the sources are non-identifiable. 6 The NHS as the deliverer of the majority of the healthcare in the UK should provide relevant information for its patients.…”
mentioning
confidence: 99%
“…Krones et al. 27 also carried out an imitation of a lay search, using the term ‘inguinal hernia’. The majority of pages did not rate highly on their standardized rating system.…”
Section: Discussionmentioning
confidence: 99%